Charge is an important determinant of hemodynamic and adverse cardiovascular effects of cationic drugs. (December 2015) - Pugsley, Michael K; Authier, Simon; Curtis, Michael J
Graphical abstract: Abstract: Cationic compounds are diverse and atypical therapeutic substances. In the present study we examined whether a prototypical class effect of cationic drugs in the cardiovascular system exists and whether this might be predictable on the basis of chemistry. The dose-dependent effects of cationic compounds of varying molecular weights and charge were examined on the blood pressure (BP), heart rate (HR) and the ECG in anesthetized rats. The compounds examined were protamine, hexadimethrine, tetraethylammonium (TEA), low molecular weight poly- L -lysine (LMW-PLL) and high molecular weight PLL (HMW-PLL). All of the compounds examined except TEA produced a dose-dependent reduction in BP. No changes occurred in HR even when high doses were administered. The ECG effects of these cationic compounds included a dose-dependent prolongation of the QT interval, especially at higher doses. All compounds transiently decreased the size of the P-wave after i.v. bolus administration whereas only protamine and hexadimethrine prolonged the PR and QRS intervals and only at the highest dose (32 mg/kg) administered. All cationic compounds, except TEA and saline, evoked ventricular premature beats (VPB), and protamine and HMW-PLL also evoked brief episodes of ventricular tachycardia (VT). The incidence and frequency of arrhythmias was not dose-dependent and no animals experienced protracted episodes of arrhythmia incidence. These dose dependent effects of the polycationic compounds tested suggest a collective mechanism of action that relates the effect of charge of the compound to the onset and persistence of observed cardiovascular toxicity, and adverse cardiovascular effect risk appears to be predictable on this basis.